Genealogy, Dendritic Cell Priming, and Differentiation of Tissue-Resident Memory CD8+ T Cells - Enamorado, Michel; Khouili, Sofía C.; Iborra, Salvador; Sancho, David (Frontiers in Immunology, 2018)
Tissue-resident memory CD8+ T (Trm) cells define a distinct non-recirculating subset. Trm cells constitute a first line of defense against local infections in barrier tissues, but they are also found in non-barrier tissues and play a role in anti-tumor immunity. Their differentiation in tissues and their phenotypical, transcriptional and functional characteristics are the object of active research. Herein, we will discuss the potential existence of committed CD8+ Trm precursors and the genealogy of memory CD8+ T cell subsets. In addition to the priming of naive T cells, there is some plasticity of antigen-experienced effector and memory T cell subsets to generate Trm precursors. Local inflammation, antigen presentation and cytokines drive Trm differentiation. It is of prime interest how specific dendritic cell subsets modulate priming and differentiation of Trm cells, as well as their reactivation within tissues. Research on how we can manipulate generation of memory T cells subsets is key for improved vaccination strategies.